(untitled) (Revista Argentina de Cirugía, 2021)
Background: the problems of reconstructive surgery for the midface are variable and can be very complex. The anatomical proximity of the midface to the orbit, base of the skull and maxillary sinuses is a challenge for the surgeon who must perform a curative resection. Objective: The aim of this presentation is to report the survival rate and disease-free interval in T4a and T4b neoplasms of the palate and paranasal sinuses consecutively resected over a 30-year period. Material and methods: Surgery was extended to the orbit in 85.2%, the skull in 8.3%, the neck in 18.7% and the parotid gland in 7.3%. Soft tissue reconstruction was performed using free flaps in 32.5%, muscle flaps in 21.6%, local flaps in 20.2%, musculocutaneous flaps in 14.7% and skin flaps in 11.3%. Results: Local and general complications were reported, and 4/203 patients (2%) died. At 5 years, overall survival was 62.5% and disease-free survival was 53%. Univariate analysis revealed that lack of previous treatment was significantly associated with recurrence and squamous cell carcinoma was a predictor of survival. Conclusions: The indication of exenteration is mandatory in the presence of ophthalmoplegia or involvement of the orbital content. Survival at 5 years is acceptable, considering the advanced stages of the disease. In some patients, previous treatments were associated with adverse outcome. Primary surgery plays an essential role for disease-free survival.